1953
DOI: 10.18174/njas.v1i3.17866
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming land flooded with salt water.

Abstract: Controlled experiments and field experience in the Netherlands have shown that the maximum concentration of salt (NaCl) in the moisture of the 5-20 cm. soil layers at which a given spring crop may be sown without risk of failure varies from year to year according to the climatic conditions prevailing in the summer. Crops which succeed in a normal season when sown at a given salt concentration in the soil moisture, may fail when a hot, dry summer follows a spring sowing at the same concentration. A table is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…per litre a satisfactory permeability was obtained. In the reclamation of sea‐flooded soil in Holland, van Beekom et al (1953) found that, ‘The typical heavy decline in structure begins in the first winter after drainage when the soluble salts are largely removed from the top soil. Its first signs occur as soon as the concentration of common salt drops below 5 g. per litre.’ This corresponds to 80 m.e.…”
Section: Permeability Of Mixed Ion Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…per litre a satisfactory permeability was obtained. In the reclamation of sea‐flooded soil in Holland, van Beekom et al (1953) found that, ‘The typical heavy decline in structure begins in the first winter after drainage when the soluble salts are largely removed from the top soil. Its first signs occur as soon as the concentration of common salt drops below 5 g. per litre.’ This corresponds to 80 m.e.…”
Section: Permeability Of Mixed Ion Systemsmentioning
confidence: 99%
“…It is necessary to consider to what extent this curve can be applied to soils other than Sawyers 1. From the work of van Beekom et al (1953) and Emerson (1954) it is obvious that soils with high organic matter or soils just out of grass have more favourable properties when saturated to varying degrees with sodium than other arable soils in a similar condition. However, for soils of semi‐arid and arid areas to which this work should mainly apply, the relationship is probably directly applicable with the possible exception that kaolinitic soils of low pH may not be as badly affected as soils containing other clay minerals.…”
Section: Permeability Of Mixed Ion Systemsmentioning
confidence: 99%